Contribution for the characterization of carolino rice cultivars - Santos, Tania (2013)
The objective of this work was to evaluate the grain biometric characteristics of 62 rice cultivars, which cover Indica and Japonica subspecies, and different types of commercial rice like, Agulha (Indica rice cultivars), Carolino (Japonica cultivars), aromatic (basmati and thai), integral rice, risotto, glutinous (waxy), wild and parboiled rice. It was noticed that for the same group type of rice there are a great variance. Generally, the Agulha, Aromatic and Integral rices commercialized in Portuguese trade are long (length high than 6 mm and length/width ratio higher than 3) and risotto cultivars are medium size. The two studied glutinous rice cultivars presented one cultivar long and other cultivar round (length lower than 5 mm and length/width ratio lower than 1.9). All rice cultivars presented high values of white vitreous, total whiteness, and low percentage of chalky area, presenting a crystalline and translucent aspect, but there is an exception to integral rice cultivars due to absence of polish operation during the milling process and for parboiled rice cultivars due to the effects of parboiled treatment. Moreover the vitreous percentage was also high. There was a strong correlation between the white vitreous values and total whiteness.